The Quest for Managing Stroke through A Mobile Device Application: A Review Study of Innovative Technologies Related to Cerebrovascular Accident - Amir Gohardani; Jin Woo Sung (Westcliff University, 2019)
Stroke, also known as a cerebrovascular accident (CVA), is the fifth leading cause of death for Americans, accounting for 140,000 lives each year ("Stroke facts," 2017). CVA marks 1 out of every 20 deaths and nearly 75% of all strokes occur in people aged 65 years and above (Centers for disease control," 2017). As a leading cause of long-term disability, stroke can have devastating effects on patients and their caregivers. Despite a number of emerging technologies that could potentially be helpful in the prevention, evaluation, and rehabilitation of strokes, typically, such technologies are limited and only considered for millennials. Similarly, at the present time, there is not a single platform designed specifically for stroke management. This makes access to relevant CVA information for baby boomers and the elderly challenging and the potential edification process rather inefficient. The key objective of this review is to identify and discuss effective technologies that can assist baby boomers, born between 1946 and 1964 in the United States, to manage CVA and further explore possible concerns of baby boomers associated with awareness and accessibility of the aforementioned technologies.